English Language Literacies – Practices, Competencies vs Demands in Academic Discourses - Haliza Harun; Hazleena Baharun; Normazla Ahmad Mahir; Hazlina Abdullah; Norhaili Massari; Fariza Puteh Behak; Suraini Mohd Ali; Ramiaida Darmi; Habibah Ismail; Noor Saazai Mat Saad; Hayati Ismail (USIM PRESS, 2024)
Vol. 6 No. 2 (2021): Jurnal Sains Insani